2021
DOI: 10.1111/jce.15273
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of ventricular tachycardia in patients with postinfarction left ventricular aneurysm

Abstract: Background: While ventricular tachycardia (VT) in the setting of postmyocardial infarction left ventricular aneurysms (LVA) is not uncommonly encountered, there is a scarcity of data regarding the safety, efficacy, and outcomes of ablation of VT in this subset of patients.Methods: Our study included consecutive patients aged 18 years or older with postmyocardial infarction LVA who presented to Mayo Clinic for catheter ablation of VT between 2002 and 2018.Results: Of 34 patients, the mean age was 70.4 ± 9.1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Ventricular aneurysms are commonly associated with recurrent VT due to reentry involving surviving myocites inside the aneurysm or at its edge. 7,[20][21][22] In the subset of patients with LV aneurysms in our study (n = 10), standard bipolar voltage mapping in sinus rhythm showed dense scar electrograms in 59.7% of mapping locations inside the aneurysm (Figure 2, panel C). However, microelectrode mapping allowed the detection of significantly higher voltages in the same locations.…”
Section: Impact Of Microelectrode Mapping and Temperature-controlled ...mentioning
confidence: 69%
“…Ventricular aneurysms are commonly associated with recurrent VT due to reentry involving surviving myocites inside the aneurysm or at its edge. 7,[20][21][22] In the subset of patients with LV aneurysms in our study (n = 10), standard bipolar voltage mapping in sinus rhythm showed dense scar electrograms in 59.7% of mapping locations inside the aneurysm (Figure 2, panel C). However, microelectrode mapping allowed the detection of significantly higher voltages in the same locations.…”
Section: Impact Of Microelectrode Mapping and Temperature-controlled ...mentioning
confidence: 69%
“…It may be the site of origin for ventricular tachycardia 2 . Antiarrhythmic drugs and radiofrequency catheter ablation are frequently used to reduce ventricular tachycardia frequency and shocks in patients with implantable cardioverter‐defibrillators 3 …”
Section: Diagnosismentioning
confidence: 99%
“…Most cardiomyopathies are predisposed to developing VT and include, among others, arrhythmogenic right ventricular cardiomyopathy, dilated cardiomyopathy, and hypertrophic cardiomyopathy [ 3 ]. In addition, left ventricular aneurysms (LVAs) and pseudoaneurysms are two complications of MI that can lead to serious morbidity and even death [ 4 ]. LVA formation involves the dilation of the ventricular wall that leads to a well-delineated outward bulging of the affected LV wall due to myocardial thinning and scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…LVA formation involves the dilation of the ventricular wall that leads to a well-delineated outward bulging of the affected LV wall due to myocardial thinning and scar formation. LVA that develops after myocardial infarction may lead to VT, among other complications including thrombus formation [ 4 ]. LVAs themselves are potential arrhythmogenic substrates and, given their complex and often apical anatomy, may be difficult to target from the endocardium [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation